2006
DOI: 10.1186/1471-2350-7-16
|View full text |Cite
|
Sign up to set email alerts
|

A study of 82 extended HLA haplotypes in HFE-C282Y homozygous hemochromatosis subjects: relationship to the genetic control of CD8+ T-lymphocyte numbers and severity of iron overload

Abstract: Background: It has been recently demonstrated that CD8+ T-lymphocyte numbers are genetically transmitted in association with the MHC class I region. The present study was designed with the objective of narrowing the region associated with the setting of CD8+ T-lymphocyte numbers in a population of C282Y homozygous hemochromatosis subjects, in whom a high prevalence of abnormally low CD8+ T-lymphocyte counts has been described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 38 publications
7
37
1
Order By: Relevance
“…12 Finally, a study of C282Y homozygous hemochromatosis subjects demonstrated a significant association between the A*02 allele and a lower CD 8 þ T-lymphocyte count. 13 This association was not observed in healthy controls carrying the A*02 allele, indicating that the lower count may be related to a locus in LD with the A*02 allele. We identified one published report 14 of an association between the B*5802 allele and higher viral load in HIV-1 subtype C-infected Zambians, although the B*5801-Cw*03 haplotype was associated with lower viral load.…”
Section: Discussionmentioning
confidence: 92%
“…12 Finally, a study of C282Y homozygous hemochromatosis subjects demonstrated a significant association between the A*02 allele and a lower CD 8 þ T-lymphocyte count. 13 This association was not observed in healthy controls carrying the A*02 allele, indicating that the lower count may be related to a locus in LD with the A*02 allele. We identified one published report 14 of an association between the B*5802 allele and higher viral load in HIV-1 subtype C-infected Zambians, although the B*5801-Cw*03 haplotype was associated with lower viral load.…”
Section: Discussionmentioning
confidence: 92%
“…However, further study is required to determine the linkage disequilibrium between HFE mutations and these genes. Moreover, recent studies of C282Y/C282Y patients have identified immunologic changes, such as lower CD8 T-lymphocyte numbers (Cruz et al 2006) and reduced expression of MHC class I molecules on the surface of blood mononuclear cells (de Almeida et al 2005). Finally, it was recently reported that patients infected with HCV genotype 3a had higher expression of hepatic MHC class I and HFE (Cardoso et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Graphs show the plots of the least square straight lines, the 95 % confidence bands and the 95 % prediction bands leading to increased iron absorption is not corrected or iii) there is somehow an additional direct impact of the mutated HFE on the iNKT cell pool such as observed in CD8+ T lymphocyte populations [29]. This hypothesis could be in line with other immune cell defects consistently described in HH [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 59%
“…They were all Caucasians from the north of Portugal, with confirmed homozygosity for the C282Y HFE mutation and no confounding co-morbidities. Clinical evaluation of the group of patients was previously described [21][22][23][24]. Twenty were males and 8 were females, with a mean age of 58 years old (range 39-80).…”
Section: Population Studiedmentioning
confidence: 99%